Improving Scientific Article Writing Skills for Science Teachers in Banjarnegara Regency through Project-Based Learning - Budi Astuti; Langlang Handayani; Ani Rusilowati; Sutikno Sutikno; Budi Naini Mindiyarto; Agus Yulianto; Ellianawati Ellianawati; Sugiyanto Sugiyanto; Nur’ainiyyah Hasni; Shelly Salista Rahmayanti; Candra Fanleon (Universitas Negeri Semarang, 2024)
There are three main elements of activities assessed in assigning credit points to teachers. First is education, second is learning and third is continuous professional development. Education and learning are activities that are usually carried out by a teacher. However, not many teachers are still doing sustainable professional development. One of them is in scientific publications. For this reason, a service was carried out regarding training in writing scientific papers to increase the acquisition of credit scores for Banjarnegara Regency MGMP Science teachers. The training methods applied include planning, implementing training and mentoring and monitoring. Based on the service carried out, it was found that the length of time teaching did not show a positive relationship with writing ability and quantity of publications. Through this service, teachers already have the motivation to start writing even though there have been no published results from this service activity.